Colin P. A. Jones: Obey, Not Know: Essays on Japanese Law and Society - Baum, Harald (Zeitschrift für Japanisches Recht, 2021)
Kurodahan Press, 2019, 439 + xiii pp., US 25.00 / € 20,86 (Amazon), ISBN: 978-4-909473-08-0